Mid Holocene vegetation reconstruction from Vanevan peat (south-eastern shore of Lake Sevan, Armenia). (22nd February 2016) - Leroyer, Chantal; Joannin, Sébastien; Aoustin, David; Ali, Adam A.; Peyron, Odile; Ollivier, Vincent; Tozalakyan, Petros; Karakhanyan, Arkady; Jude, Fany
Abstract: A sediment core has been retrieved from Vanevan peat (south-eastern shore of Lake Sevan, Armenia), which is today disconnected from Lake Sevan thanks to an artificial shallowing of the lake. Based on 5 radiocarbon dates, Vanevan record covers the Mid Holocene (from ca. 7800 to ca. 5100 cal. BP). The Late Holocene is today absent in the peat stratigraphy due to modern peat exploitation by surface mining. This study focuses on a multi-proxy approach including pollen, charcoals, and pollen-inferred climate reconstruction. An open-land, steppic vegetation is recorded up to ca. 7700 cal. BP, followed by a more forested landscape during the Mid Holocene (up to ca. 5700 cal. BP), and ending again with an open-land vegetation (to the end of record, 5100 cal. BP). This vegetation dynamics responds to general climate changes documented in the Near East. Whether human activities are documented since ca. 7500 cal. BP (Late Neolithic) in Vanevan, they remain marginal and probably did not affect the area. Early Holocene dry climate, which caused the steppic environment to be widespread through the Near East, is strongly related to low late spring precipitation (PMay–Jun  = 180 mm). Mid Holocene forested landscape and increasing lake-level seem related to late spring precipitation (+28%), which is the main change in estimated climate parameters. This has to be linked with reinforcement of the Westerlies and less active Siberian High, which are inversely involved in the following, dry phase starting at ca. 5700 cal. BP.